সোনা ঝরা দিনগুলি - আজরফ, দেওয়ান মোহাম্মদ, ১৯০৮-১৯৯৯. (ঢাকা : উৎস প্রকাশন, 2004)
Autobiography of a former principal and intellectual from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Ājarapha, Mohāmmada, -- 1908-1999.; College teachers -- Bangladesh -- Biography; Intellectuals -- Bangladesh -- Biography